TRAJECTORIES OF INDIANITY: THEOLOGY AND POLITICS - Beaucage, Pierre (Revista de Historia Social y de las Mentalidades, 2025)
In this paper, I want to esplicit the process thro ugh which the representation of indianity was historically constructed in Western imaginary, and stress the interrelation between the religious and political dimensions. The first defin ition was theological and it remained polarized between the « innocent native » and the « savage sl ave of the Devil ». Las Casas’ vision, put aside during long periods in view of the difficulti es of evangelization, was recently rescued by Theology of Liberation and one of its avatars, Indi an Theology; a lay version was eleborated by the ecologist movement. The political representatio n of the Indian, in the Spanish colonies of Mesoamerica and the Andes, was rooted in Aristotle’ s conception of men « born to obey », which corresponded to a practice of subordination . To the North and the South of the continent (excepting the interlude of French commercial articulation ), a policy of substitution was accompanied by an image of the Indian as doomed to disappear from a land « manifestly destined » to European settlers. Present-day indigenous orga nizations develop a self-representation which combines lascasian-ecologist elements about their p recolonial past with the modern concept of nation and its corollaries, territory and self-dete rmination.